2004
DOI: 10.1063/1.1647269
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of soft x-ray emission characteristics in a low energy dense plasma focus device

Abstract: An investigation on the soft x rays emitted in a 2.2 kJ Mather-type dense plasma focus device using a multichannel diode spectrometer and a simple pinhole camera is reported. Emitted x rays associated with different shapes (hollow, solid, and hemispherical) of anode and in hydrogen/nitrogen gas medium are compared. The structure of x-ray emitting sites as well as x-ray yields were found to be strongly influenced by the shape of the anode and the filling gas pressure. The maximum yield of 2.2 J into 4π sr was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…It is seen that both the quantities are strongly dependent on pressure and they are maximum at around 0.3 Torr. In case of X-rays and ion beam emission from plasma focus device, similar types of pressure dependence behavior have been also observed and re- ported elsewhere [20,23]. The highest electron beam charge and density are around 7.5 mC and 4.5 × 10 16 m −3 , respectively.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…It is seen that both the quantities are strongly dependent on pressure and they are maximum at around 0.3 Torr. In case of X-rays and ion beam emission from plasma focus device, similar types of pressure dependence behavior have been also observed and re- ported elsewhere [20,23]. The highest electron beam charge and density are around 7.5 mC and 4.5 × 10 16 m −3 , respectively.…”
mentioning
confidence: 58%
“…1. Further details about our plasma focus device have been published elsewhere [20,23]. The experiment was performed in a nitrogen gas medium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, material and shape of electrodes, proper selection of anode and insulator sleeve length, and preionization before initial discharge are considered to be important in symmetric development and acceleration of current sheath, in addition to normal operating conditions [13][14][15][16]. Hill and Hubbs [17] developed a PF, which was fired repeatedly without purging the test gas between the shots.…”
Section: Introductionmentioning
confidence: 99%
“…An important part of the recent experimental studies on x-ray and particle emission from PF is oriented in interesting applications such as contact microscopy, x-ray and electron beam lithography, generation of soft x-ray spectral lines of highly charged heavy metal ions, metal coating by ion sputtering, surface modification and deposition of thin films, x-ray backlighting, radiography of biological and mechanical objects, and micromachining. [8][9][10][11][12][13][14][15][16] The x-ray emission from a given PF device depends in a rather complicated way upon the design and operating parameters such as the operating voltage and bank energy, [17][18][19] the circuit inductance, 20 the working gas nature and pressure, 12,16,21 the anode dimensions, shape, and material, [22][23][24][25][26][27] the material and configuration of insulator sleeve, 28 and preionization assisted breakdown. 29,30 It is reported that when the plasma focus is operated in hydrogen with small admixture of inert gases, the x-ray emission is strongly enhanced.…”
Section: Introductionmentioning
confidence: 99%